The Principal of Risk and Profit Sharing in Islamic Banking - Eka Supriatiningsih (Ijtimā`iyya: Journal of Muslim Society Research, 2018)
The role of banking that is very strategic in achieving Indonesia's economic development goals recently, requires a careful study of banking concepts that have been operationalized, both conceptually and their applications, so as to create a strong banking system in the era of globalization in the future. The existence of Islamic banks in Indonesia has not been fully accepted, there are still some people who equate with conventional banks. Based on the background of the problem above, which is the identification of the problem in this paper, namely: 1) What is the application of the principle of sharing the results and risks in fundraising activities in Islamic banking? 2) What are the operational constraints faced in implementing profit sharing and risk principles in Islamic Banking?. Based on the discussion above, conclusions can be drawn, as follows: 1) The implementation of fundraising using the profit sharing principle in Islamic Banking is carried out using the principles of Wadiah and Mudharabah. The Wadiah principle uses the Wadiah Current Account using products such as: Singapore BSM Dollar Current Account, BSM Current Account, BSM Currency Current Account, BSM Ouro Current Account, Bank Muamalat Wadiah Deposit Account in Rupiah and Foreign Currency, personal and corporate, and Wadiah Savings Account using products like: Junior Community Savings which is a special savings for students, Simpatik Savings, BSM Dollar Savings. While the mudharabah principle uses the Tabungan Mudharabah contract using products such as: Mudharabah Savings Accounts are Hajj Savings, Investa Scholar Savings, Qurban Savings and Savings Cards and time deposits for mudharabah use products such as: Bank Syariah Mandiri Savings, BSM Foreign Currency Deposits and Mudharabah deposits. In calculating profit sharing only in Mudharabah principles, the wadiah principle is only a bonus given to the bank's willingness. The pattern of calculation for results is to use the principle of profit sharing, which means that the results are calculated from the total income of the fund management and the amount of profit sharing depends on the initial agreement, 2) There are a number of operational constraints faced by Sharia Banking in financing Financing Results such as limited human resources, Islamic Banking management, limited Office Networks, and still weak government regulations on Islamic Banking.